Right to Health: reflections on health care for elderly people with HIV/AIDS (Research, Society and Development, 2022)
In recent years, the virus that causes AIDS (HIV) has become more expressive in the elderly, a fact that has not progressed with the improvement in medical care sufficiently to combat it, raising questions about the quality of medical interventions in the care of the elderly. Because of this, this study aimed to discuss the importance of medical interventions in the health care of elderly people with HIV/AIDS. This is a narrative review, the data collection process carried out from September to December 2021, with access to the following platforms: SciELO, PubMed, Google Scholar, Virtual Health Library and DATASUS. In the analyzed studies, the findings were that, due to unpreparedness in working with issues related to the sexuality of the elderly, either by age difference and/or gender, many professionals expose the elderly to vulnerabilities: higher risk of exposure to the virus due to lack of information on the subject and negligence in diagnoses, such as, for example, such invisibility of the sexuality of the elderly is reflected in anti-HIV serology not being routine in primary care, compromising the diagnosis and early treatment of HIV/AIDS with maintenance of the chain of contamination and transmission of the virus among this population. It is concluded that the need for professionals to address various issues related to the life of the elderly, to contemplate the various dimensions of their existence including sexuality, and that managers should develop public policies that favor such an approach.